Veniamin Costachi: repères généalogiques, l'enfance, l'adolescence et les premières années de la maturité - Mirela Beguni (Codrul Cosminului, 2009)
This study presents some genealogical aspects, childhood, adolescency and first years of maturity of the illustrous hierarch of Moldavia, the metropolitan Veniamin Costachi, highly appreciated by our historiography and considered among the biggest and most important personalities of the Romanian Orthodox Church.